Clot retraction - Budtz-Olsen, Otto Egede (Department of Pathology, 2020)
The haemorrhagic disorders form only a small, although often most alarming part of the diseases inflicted upon mankind, and in spite of the enthusiasm of the disproportionally great number of workers investigating the problem of the coagulation of the blood, this problem until quite recently could only be looked upon as being mainly of academic physiological interest. With the advent and daily increasing use of the highly dangerous anti-coagulant therapy for thrombosis and embolism, demanding at least a general understanding of the mechanism of blood clotting, every aspect of this mechanism has become of practical clinical importance, and no serious effort to clarify the question can be considered wasted. It is peculiar that the last phase of coagulation, the contraction of the clot, which is by no means the least spectacular, has received rather scanty attention compared to the enormous amount of work that has been expended on the earlier stages. No agreement exists with regard to the mechanism or purpose of clot retraction; the factors controlling it are to a large-extent unknown, and even the fundamental question of the part played by the platelets is undecided.